Roundup 2022: Agricultural Research Center-Hays (Kansas Agricultural Experiment Station Research Reports, 2022)
Roundup is the major beef cattle education and outreach event sponsored by the Kansas State University Agricultural Research Center - Hays. This report communicates timely, applicable research information on beef production and rangeland topics.
Keywords: beef cattle; pastures; weeds; bluestem; stocker; feedlot